การเมืองในกระบวนการกำหนดนโยบายขององค์การบริหารส่วนจังหวัดปทุมธานี - วงษ์พาณิทอักษร, นันท์นภัส (Academic Journal Phranakhon Rajabhat University, 2016)
การศึกษาเรื่องการเมืองในกระบวนการกำหนดนโยบายขององค์การบริหารส่วนจังหวัดปทุมธานี วัตถุประสงค์เป็นการศึกษาว่า นโยบายของจังหวัดถูกกำหนดขึ้นอย่างไร จากชนชั้นใด กลุ่มไหน มีวิธีการหรือขั้นตอนในการกำหนดนโยบายอย่างไร มีปัจจัยใดเข้ามาเกี่ยวข้องบ้าง รวมทั้งศึกษาว่ามีการเมืองระดับชาติเกี่ยวข้องอย่างไร มีกลุ่มใดบ้างและมีการรวมกลุ่มกันอย่างไร ส่งผลอย่างไรต่อกระบวนการตัดสินใจในเชิงนโยบาย โดยใช้วิธีวิจัย คือ การศึกษาจากเอกสารที่เกี่ยวข้อง การสัมภาษณ์ และการสังเกต ผลการวิจัยสรุปได้ว่า 1. การกำหนดนโยบายขององค์การบริหารส่วนจังหวัดถูกกำหนดจากชนชั้นนำในองค์การบริหารส่วนจังหวัด กล่าวคือ ฝ่ายบริหาร และฝ่ายนิติบัญญัติขององค์การบริหารส่วนจังหวัด 2. การกำหนดนโยบายขององค์การบริหารส่วนจังหวัด คือ การกำหนดนโยบายเพื่อการกระจาย และจัดสรรผลประโยชน์แก่สมาชิกสภาองค์การบริหารส่วนจังหวัดอย่างลงตัวจนเป็นที่พอใจกับทุกกลุ่ม 3. นักการเมืองระดับชาติได้เข้ามามีบทบาทต่อองค์การบริหารส่วนจังหวัด เนื่องจากฐานคะแนนเสียง และผลประโยชน์ต่าง ๆ ของนักการเมืองระดับชาติ และนักการเมืองท้องถิ่นมีความทับซ้อนและเกื้อหนุนกัน Studying of the politic in policy making process of Pathumthani Provincial Administration Organization have the objectives to study how the policy of Pathumthani Provincial administration Organization has stipulated from which ranks, which groups of society. How about the method and process to stipulated a policy? What factors are related with this matter? How many groups has stipulated it and how do they grouped together? How do there have any effects to the decision policy process? On this regards, researching by studied from relevant documents, interviewing and observation The studied results can summarized as follows: 1. A policy process of Pathumthani Provincial Administration Organization has stipulated by the elites in the Provincial Administration Organization. Which are the Administration and the Legislation of the Provincial Administration Organization 2. The policy of Provincial Administration Organization are to distribute and to allot benefits to members of assembly of Provincial Administration Organization as equivalent and satisfaction to the stakeholders. 3. The nation politicians has become a role the part of Provincial Administration Organization. Due to the votes and benefits of the nation politicians and the local politicians are overlap and they do a favor with each other.